Efektivitas Ekstrak Putri Malu (Mimosa pudica Linn.) sebagai Nefroprotektor pada Tikus Wistar yang Diinduksi Parasetamol Dosis Toksik - Ari Setyo Rini; Hairrudin Hairrudin; Sugiyanta Sugiyanta (Pustaka Kesehatan, 2013)
The ethanolic extract of Mimosa pudica Linn. was evaluated for its nefroprotective and antioxidant activity against paracetamol induced kidney toxicity in wistar rats. Liver damage was induced by administration of 1.350 mg paracetamol/kg body weight. The ethanolic extract of Mimosa pudica Linn. (400mg/kg, 600mg/kg, and 800 mg/kg) was administered orally to the rats for 6 days. Curcuma® was given as positive control. All of the test drugs were administered orally by suspending in 1% of Na CMC solution. The nefroprotective activity was assessed using the levels of BUN and creatinine serum. The result revealed that all doses of the extracts showed effective activity in inhibiting the increase of BUN and creatinine serum and the doses of 800 mg/kg showed the biggest percent value (9,4% of BUN level and 12,19% of creatinine level). The positive control group could prevent the increase of BUN and creatinine serum better when compared with the group of Mimosa pudica Linn.The result of the present study indicated that the ethanolic extract of Mimosa pudica Linn. significantly prevent the increase of the level BUN and creatinine serum in wistar rats induced with paracetamol toxic dose.Keywords: Antioxidant, nefrotoxic, Mimosa pudica, paracetamol, BUN, creatinine.